Feasibility of continuous non-invasive delivery of oxygen monitoring in cardiac surgical patients: a proof-of-concept preliminary study - Roderica R. G. Ng; Suneel R. Desai; Felicia S. W. Chu; Ming Ann Sim; Sheryl W. L. Chee; Jerry Y. H. Fuh; Lian-Kah Ti; Sophia T. H. Chew (BMC Anesthesiology, 2024)
Abstract Purpose Oxygen delivery (DO2) and its monitoring are highlighted to aid postoperative goal directed therapy (GDT) to improve perioperative outcomes such as acute kidney injury (AKI) after high-risk cardiac surgeries associated with multiple morbidities and mortality. However, DO2 monitoring is neither routine nor done postoperatively, and current methods are invasive and only produce intermittent DO2 trends. Hence, we proposed a novel algorithm that simultaneously integrates cardiac output (CO), hemoglobin (Hb) and oxygen saturation (SpO2) from the Edwards Life Sciences ClearSight System® and Masimo SET Pulse CO-Oximetry® to produce a continuous, real-time DO2 trend. Methods Our algorithm was built systematically with 4 components – machine interface to draw data with PuTTY, data extraction with parsing, data synchronization, and real-time DO2 presentation using a graphic-user interface. Hb readings were validated. Results Our algorithm was implemented successfully in 93% (n = 57 out of 61) of our recruited cardiac surgical patients. DO2 trends and AKI were studied. Conclusion We demonstrated a novel proof-of-concept and feasibility of continuous, real-time, non-invasive DO2 monitoring, with each patient serving as their own control. Our study also lays the foundation for future investigations aimed at identifying personalized critical DO2 thresholds and optimizing DO2 as an integral part of GDT to enhance outcomes in perioperative cardiac surgery.